Rogue strike - Ricciardi, David (New York Berkley, an imprint of Penguin Random House LLC, 2020)
CIA agent Jake Keller and his partner, Curt Roach, are in Yemen on an important mission. They've been tipped off to a secret meeting of top ISIS leaders. The plan is to interrupt the meeting with a few unexpected visitors-a pair of Hellfire missiles from an orbiting drone. But the drone stops responding to their signals and soon disappears over the horizon. When next seen, the drone is attacking innocent pilgrims in Mecca. Jake and Curt are staggered. The U.S. government is desperate to disavow this atrocity. Who better to blame than a couple of rogue CIA agents? With all the governments of the Middle East looking for them and no help from their own side, they are in a desperate race to stay ahead of the mob and find out who's actually behind the crime.
112662
Keywords: United States. -- Central Intelligence Agency -- Officials and employees -- Fiction; Terrorism -- Prevention -- Fiction; Drone aircraft -- Fiction; Conspiracies -- Fiction; Aircraft theft -- Fiction; Intelligence officers -- Fiction; Undercover operations -- Fiction; Drones -- Romans, nouvelles, etc; Conspiration -- Romans, nouvelles, etc; Employees; Aircraft theft; Spies -- Fiction; Americans -- Fiction; Bombs -- Fiction; International relations -- Fiction; United States; Thrillers (Fiction); Fiction; Political fiction; Suspense fiction; Novels; Romans